ANALISIS PENERAPAN GOOD GOVERNANCE DALAM PENYUSUNAN ANGGARAN SKPD PEMERINTAH KOTA BITUNG - Boyoh, Jonathan Karlo; Saerang, David P. E.; Warongan, Jessy D. L. (Universitas Sam Ratulangi, 2023)
The purpose of this gacorwin study is to determine the application of Good Governance in the preparation of the budget of the SKPD of the Bitung City Government. This type of research is research using qualitative methods and descriptive approaches. To obtain the necessary data, researchers conducted data collection activities by means of participatory observation, in-depth interviews, and documentation analysis. The results of this study show that the application of Good Governance in the preparation of the budget of the Regional Apparatus Work Unit (SKPD) of the Bitung City Government from 9 principles of Good Governance, Principles of Participation, Principles of Accountability/Responsibility, Principles of Openness/Transparency, Principles of Law Enforcement, Principles of Responsiveness, Principles of Agreemen /Deliberation gacorwin Orientation, Principles of Effectiveness and Efficiency, Principles of Strategic Vision have been done well, but the Principles of Equality of Justice have not been done as it should. The results of this study also found that there is a lack of synergy in preparing budgets by SKPD with third parties, so SKPD must gacorwin increase synergy with third parties in preparing each budget. Furthermore, researchers found that human resources at the SKPD of the Bitung city government still do not understand digital technology, this greatly affects every existing performance so that the implementation of Good Governance in the preparation of the Bitung City Government SKPD budget can run well. Furthermore, the Bitung city government must see and survey the field related to the price of goods so that in preparing the budget with the program to be prepared by the government can run in accordance with the vision and mission of the Bitung city government